Functional and Oncological Outcomes of Open Partial Laryngectomy vs. Transoral Laser Surgery in Supraglottic Larynx Cancer - Muhammet Fatih Gökmen; Zahide Çiler Büyükatalay; Süha Beton; Mustafa Kürşat Gökcan; Gürsel Dursun; Cem Meço; Tarık Babür Küçük (Turkish Archives of Otorhinolaryngology, 2020)

(untitled)
Objective: The aim of the presented study was to evaluate the outcomes of open partial laryngectomy (OPL) versus transoral laser surgery (TLS) in patients operated on for supraglottic laryngeal carcinoma based on functional parameters (duration of hospitalization, oral nutritional status and duration of transition to oral feeding, weaning status and duration after tracheotomy, and postoperative voice results) and oncological results (overall survival rate, disease-specific survival rate, recurrence, and presence of second primary tumors) in both groups.Methods: All laryngeal carcinoma patients who had undergone either OPL or TLS in the period from January 2012 to March 2017 in our center and were followed-up at least for 36 months were included in the study. Statistical analyses were carried out using the t-test and the Mann-Whitney U test to compare the means, and the Kaplan-Meier test for survival analysis.Results: Fifty patients (44 males and 6 females) met the study criteria, of whom 31 had undergone OPL and 19 TLS. Patients that underwent TLS had less tracheotomy needs, needed shorter hospitalization periods, and transitioned to oral feeding earlier, compared to those that underwent OPL. There were no significant differences between the two groups based on oral feeding rates and voice outcomes. The impact of TLS and OPL on organ preservation in supraglottic laryngeal cancer were comparable. For local recurrences, repeated endolaryngeal laser surgeries and adjuvant treatments could be used in the TLS patient group. There were no significant differences between the two groups based on overall survival rate and disease specific survival rate.Conclusion: Although no significant differences were found in our study between the two surgical procedures in terms of oncological outcomes, TLS appeared to produce better functional outcomes in supraglottic laryngeal carcinoma than OPL.